Joanne K. Rowling's Septology as a Boundary-Crossing Cultural Event (KULT_online, 2012)
In 2010, three years after the publication of the last volume in the Harry Potter series, the authors of this study turned their attention to Joanne K. Rowling and posed previously unanswered questions: How does a work totaling several thousand pages capture an international readership? Why does Rowling's magical universe hold such fascination for readers in a world dominated by technology and the sciences? Ina Karg and Iris Mende find their answers in the analysis of public discourse from the last year of publication, as well as in the texts themselves. As a result, they demonstrate that Harry Potter became a cultural phenomenon because the series (1) crossed literary boundaries (the books are components of a comprehensive set of consumer goods); (2) removed boundaries between readers (drawing fans not only from all over the world, but also from different age groups and social classes); and, (3), because the texts in their own right shatter genre boundaries and literary traditions.